2006
DOI: 10.1079/bjn20051663
|View full text |Cite
|
Sign up to set email alerts
|

Yoghurt accelerates the recovery of defence mechanisms againstStreptococcus pneumoniaein protein-malnourished mice

Abstract: Experiments studied the effect of yoghurt on the recovery of defence mechanisms against Streptococcus pneumoniae respiratory infection in malnourished mice. Weaned mice were malnourished with a protein-free diet (PFD) for 21 d. Malnourished mice were made replete with a balanced diet (BD), yoghurt, or the BD with supplemental yoghurt (BD þ Y) for 7, 14 or 21 d. The normal control (NC) group was fed the BD whereas malnourished control (MC) mice consumed only the PFD. Mice were challenged with pneumococci at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 43 publications
3
46
1
2
Order By: Relevance
“…TLC, DLC were all decreased in both malnourished and malnourished mice infected with Giardia which may be due to a protein deficient diet that alters the blood and serum biochemical leading to hypoprotienemia and hypoalbuminia [17,13,22]. Study on the organ mass also showed decreased weight in malnourished and malnourished mice infected with Giardia.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…TLC, DLC were all decreased in both malnourished and malnourished mice infected with Giardia which may be due to a protein deficient diet that alters the blood and serum biochemical leading to hypoprotienemia and hypoalbuminia [17,13,22]. Study on the organ mass also showed decreased weight in malnourished and malnourished mice infected with Giardia.…”
Section: Discussionmentioning
confidence: 85%
“…The mice were housed under the standard condition of light and dark cycle and were fed with the standard pellet diet, (Hindustan Lever Products, Limited, Kolkata, India) and 4.3% protein diet (Ashirwad Private Limited, Kharar Punjab, India formulated as per Villena et al and water ad libitum [13]. The standard pellet diet comprises of proteins (230 g/kg), carbohydrates (538 g/kg), lipids (50 g/kg), vitamin mixture (22 g/kg) and mineral mixture (40 g/kg), while protein free diet contain 43 g/kg of protein and 758 g/kg of carbohydrates with the rest of the nutrients in the same composition.…”
Section: Introductionmentioning
confidence: 99%
“…Además, estudios en ratones desnutridos a los que se les suministró una dieta balanceada con yogur probiótico incrementaron la función bactericida de los fagocitos bronco-alveolares. Los macrofagos alveolares constituyen la primera línea de defensa contra agentes infecciosos que tienen acceso a las vías respiratorias por el intercambio gaseoso (Villena et al, 2006). Otro estudio clínico demostró que la ingestión de Bifidobacterium longum aumentó el número de macrofagos en los pulmones (de Vrese y Schrezenmeir, 2002).…”
Section: Efectos Beneficiosos De Los Probióticosunclassified
“…Sigue siendo cuestión de debate el mecanismo por el cual el producto probiótico tiene un efecto contra las infecciones respiratorias. Una hipótesis es que el probiótico favorece los mecanismos inmunomoduladores implicados en la protección contra las infecciones respiratorias (Villena et al, 2006).…”
Section: Efectos Beneficiosos De Los Probióticosunclassified
“…However, several zootechnical studies have reported controversial results regarding digestibility and increases in body mass in animals used for human consumption (Kamra et al 1996, De Brito et al 2005, Sanches et al 2006, Budiño et al 2006, Huaynate et al 2006, Zanato et al 2008. Additionally, several studies have shown that probiotics stimulate the immune system (Erickson and Hubbard 2000, Cano and Perdigón 2003, Villena et al 2006, De Souza et al 2007, Dewan et al 2007, Kaburagi et al 2007, Pitsouni et al 2009), which could contribute to prevention or even treatment of bowel infection, which is another problem to consider in cases of malnutrition associated with anatomical and functional bowel disorders (Chandra 1992). In addition, other studies suggest that probiotics might contribute to the integrity of the intestinal barrier (Menningen and Bruewer 2009) and that they are efficacious in treating inflammatory bowel diseases (Resta-Lenert and Barrett 2009).…”
mentioning
confidence: 99%